Impression Management in the Communications Services for New Student Admissions at Private Universities in West Java - Tresna Wiwitan; Sophia Novita; Khalifia Rahma Nidya (Jurnal Riset Public Relations, 2026)
Abstract. Currently, societal interaction patterns, especially those of colleges, affect how people perceive an institution. Institutions must be able to harmonize all internal elements by positioning Private University as a service institution that is able to "serve" stakeholders and meet their needs effectively. Impression Management theory is used to analyze the research results, where Public Relations practitioners must be capable of creating positive impression among the parties they communicate with on behalf of their organization. This study aimed to identify impression management in three Indonesian private universities with accreditations, as well as the inhibiting and supporting factors in new student admissions activities. Data was collected using qualitative methods through case studies, which involved in-depth interviews and observations of the committee and prospective students. The results of the study found that impression management was applied both verbally and non-verbally through various channels, including social media, websites, collaborations, scholarships, and face-to-face meetings. Nevertheless, several inhibiting factors were identified, such as study program accreditation, technological constraints, negative feedback from competitors, and inadequate facilities. On the other hand, supporting factors included infrastructure development, collaboration with high schools, online registration, and the National Selection for Universities by Invitation program for prospective students. The results of this study are expected to positively impact Indonesian private universities by improving the quality of communication and services during the admission process for newstudents.